Opinion dynamics control as a consensus problem of multi-agent systems : an LMI approach - Alkhorshid, Daniel Rostami (2022)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2022.